POLITENESS STRATEGIES IN TONY ABBOT’S SPEECH CONCERNING AUSTRALIA-INDONESIA TAPPING ISSUE - HANDOKO, PINTO ZAKIRI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Key Words: Politeness, Face Threatening Acts (FTA), Politeness Strategies, Australiatapping Indonesia issue, Political Speech, Tony Abbott’s Speech, House of Representatives Politeness as one of linguistic phenomena always exists when people communicate with each other. We can find politeness not only in face to faceconversation, but also in a speech. There are many types of speech, one of the types is political speech. This study analyzed political speech from Australia’s Prime MinisterTony Abbot and it discussed politeness strategies in Tony Abbot’s speech concerningAustralia-Indonesia tapping issue. There two problems to be solved in this study: (1)what face is being threatened in Tony Abbott’s Speech concerning Australia-IndonesiaTapping Issue and (2) what are the politeness strategies in Tony Abbott’s Speech concerning Australia-Indonesia Tapping Issue. This study applied qualitative approach in which the data were collected in the form of words or sentences. This study used document analysis in analyzing thepoliteness strategies in Tony Abbott’s Speech concerning Australia-Indonesia Tapping Issue.This study revealed that the positive face and the negative face are threatened.The positive face of the speaker and the positive face of the hearer are  threatened. Meanwhile for the negative face, only the negative face of the hearer is threatened. For politeness strategies, there are four politeness strategies that were found in this study,those are bald on record, positive politeness strategies, negative politeness strategies andoff record. Tony Abbott’s in his speech concerning Australia-Indonesia tapping issuemostly threatened positive face of the hearer and frequently used positive politenessstrategies because he wants to the hearer agree and corroborate his opinion thatAustralia intelligence is doing tapping to protect the country, advance national interest and help the allies. In other words, it is a kind of act of caring for what Australiaintelligence already did.  In this study, Tony Abbott also threatened negative face usingpositive politeness strategies. It means that there is an effort of teasing the hearer ortoward the hearer’s attitude.For the next researchers, the writer suggests that the next researcher should use the other theory which is different from this study to enrich the analysis in the further research. Also, the next researcher can use the other objects in analyzing politeness strategies and FTA.